Evaluation of industrial green development and industrial green competitiveness: Evidence from Chinese urban agglomerations - Yi Wang; Hui Hu; Wenjing Dai; Kelly Burns (Ecological Indicators, 2021)
Urban agglomerations are important regional economic units. Industrial green development and green competitiveness are of great significance to the sustainable development of urban agglomerations. This study, for the first time, uses the Entropy TOPSIS model and Theil index to reveal differences between industrial green development in China’s three major urban agglomerations. Factor and hierarchical clustering analysis is also used to evaluate and compare industrial green competitiveness in these agglomerations. Four important findings arise from the analysis. First, industrial green development is highest in Pearl River Delta, followed by Beijing-Tianjin-Hebei, and lowest in Yangtze River Delta. Beijing, Shanghai and Shenzhen have the highest industrial green development level. Second, the variation in green development is smallest between Beijing-Tianjin-Hebei and Yangtze River Delta. Cities in the Beijing-Tianjin-Hebei have more balanced industrial green development than the other two urban agglomerations. Third, industrial green competitiveness is highest in Pearl River Delta. It is superior to the Yangtze River Delta and Beijing-Tianjin-Hebei in industrial green growth competitiveness and resource and environmental pressure competitiveness. Finally, after classifying 45 major cities of urban agglomerations into four echelons by industrial green competitiveness, we find that only Beijing and Shenzhen are in the highest echelon. Shanghai and Guangzhou are in the second echelon, and Hefei, Tianjin, Hangzhou, Suzhou and Zhuhai are in the third echelon. These findings have important policy implications and we offer recommendations based on the findings.